Application of production function approach to estimate the economics of broiler production in the Rupandehi district of Nepal - Aryal, Niranjan; Dhital, Bhargav; Karna, Bimal Kumar Lal; Lamichhane, Jeevan; Khanal, Shiva (Journal of Agriculture and Natural Resources, 2023)
A study was conducted in a year 2020 A.D to analyze the application of production function approach to estimate costs and returns, resource use efficiency, and problem in broiler production. A total of 120 broiler farmers were selected representing small, medium and large farms, also 10 number of wholesalers, retailers and consumers were selected for market study and interviewed with a pre-tested questionnaire. The data were collected, entered and analyzed by using SPSS and MS-Excel. The total cost of production per bird was maximum (Rs.372.93) in small and minimum (Rs.340.96) in large farms, it was Rs.361.42 in medium farms. FCR for small farms was 1.67, for medium 1.81 and for large farms 1.89. It was further seen that the B: C ratios 1.27 for small farms, 1.25 for medium, and 1.34 for large farms. It was clear that large farm is more profitable as compare to small farm. Cobb-douglas production function analysis showed that with every other factors remaining constant an increase in 100% in the chicken cost, feed cost, vaccine cost and others cost the gross return was expected to be increased by 3.75, 8.6, 2.6 and 1.7 % respectively. The different agent involve in the marketing of broiler are producer, retailer, wholesaler, dealers, commission agent, middleman and finally consumers. The SWOT analysis was done on the basis of the interview taken by all the stakeholder in the study area of the district. In spite of broiler production potentiality, there were many constraints in production, marketing and research site which need to be addressed by enhancing technology adoption, such as targeted training programs and financial support, could contribute to sustainable broiler farming practices in the research site.